Economic Prosperity: A Global Imperative - Fish,Mary (Journal of Baha'i Studies, 1997)
Economic growth does not necessarily enhance human welfare. The Prosperity of Humankind recognizes the role of economics in igniting the capacity of humankind. The Bahá'í concept of human nature opens a dialogue between religion and economists.
Mirrored with permission from journal.bahaistudies.ca.
Keywords: Economics; Prosperity; Sustainable development